Chimeric antigen receptor T-cell therapy in autoimmune diseases - Liu, Jie; Zhao, Yan; Zhao, Hai (Frontiers in Immunology, 2024)
The administration of T cells that have been modified to carry chimeric antigen receptors (CARs) aimed at B cells has been an effective strategy in treating B cell malignancies. This breakthrough has spurred the creation of CAR T cells intended to specifically reduce or alter the faulty immune responses associated with autoimmune disorders. Early positive outcomes from clinical trials involving CAR T cells that target the B cell protein CD19 in patients suffering from autoimmune diseases driven by B cells have been reported. Additional strategies are being developed to broaden the use of CAR T cell therapy and enhance its safety in autoimmune conditions. These include employing chimeric autoantireceptors (CAAR) to specifically eliminate B cells that are reactive to autoantigens, and using regulatory T cells (Tregs) engineered to carry antigen-specific CARs for precise immune modulation. This discussion emphasizes key factors such as choosing the right target cell groups, designing CAR constructs, defining tolerable side effects, and achieving a lasting immune modification, all of which are critical for safely integrating CAR T cell therapy in treating autoimmune diseases.